2011
DOI: 10.1029/2009jd013429
|View full text |Cite
|
Sign up to set email alerts
|

Gravity and Rossby wave signatures in the tropical troposphere and lower stratosphere based on Southern Hemisphere Additional Ozonesondes (SHADOZ), 1998–2007

Abstract: Prior investigations attempted to determine the relative influence of advection and convective processes on ozone and water vapor distributions in the tropical tropopause layer (TTL) through analyses of tracers, related physical parameters (e.g., outgoing long‐wave radiation, precipitable water, and temperature), or with models. In this study, stable laminae in Southern Hemisphere Additional Ozonesonde Network (SHADOZ) ozone profiles from 1998 to 2007 are interpreted in terms of gravity waves (GW) or Rossby wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 110 publications
(201 reference statements)
2
47
1
Order By: Relevance
“…3d in Thompson et al (2011). Here, it is seen that upper tropospheric ozone concentrations are lower in months with a high frequency of deep convection.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…3d in Thompson et al (2011). Here, it is seen that upper tropospheric ozone concentrations are lower in months with a high frequency of deep convection.…”
Section: Discussionmentioning
confidence: 72%
“…Also included is the annual cycle of the LNB (red, mixing height (red, dashed), the LRM height (blue, solid), and the ozone minimum hed). (bottom) annual cycle of the ozone concentration (ppbv) at American Samoa, in Thompson et al (2011). Orange and red colors indicate relatively low values, blue latively high values.…”
Section: Discussionmentioning
confidence: 99%
“…At the sites equatorward of 15 • S/N, the ENSO signal exhibits varying characteristics, with stations responding with positive ozone and temperature anomalies (for example, Kuala Lumpur and San Cristóbal), negative at others (Natal and Nairobi in Lee et al, 2010) and with distinct time lags (Randel and . Using a different diagnostic, gravity wave frequency (GWF), as inferred from ozone and potential temperature laminae within the ozone and radiosonde profiles, Thompson et al (2011) found that ENSO signatures during the SHADOZ record were most pronounced in the TTL and less so in the MT. Over subtropical Irene and Réunion, GWF is 2-3 times lower than over Kuala Lumpur, Watukosek and San Cristóbal .…”
Section: Dynamical Factors and Trend Analysismentioning
confidence: 99%
“…8). We note that the quasi-biennial oscillation (QBO) also affects tropical ozone (e.g., Witte et al, 2008;Thompson et al, 2011). Adding a term for the QBO in the regression model, Eq.…”
Section: Dynamical Factors and Trend Analysismentioning
confidence: 99%
“…The second source involves large-scale equatorial waves, e.g. Kelvin waves (Webster, 1972;Gill, 1980;Wheeler et al, 2000;Ryu and Lee, 2010;Thompson et al, 2011), which are usually triggered by convection and organized convective systems. Equatorial Kelvin waves with time periods in the order of a few days lead to temperature anomalies of up to 8 K with typical values around 2-3 K (Immler et al, 2008) Middle panel: time evolution of ice crystal number concentration.…”
Section: Large-scale Dynamicsmentioning
confidence: 99%